Atomic Structure of Intrinsic and Electron-Irradiation-Induced Defects in MoTe(2) - Elibol, Kenan (Chem Mater, 2018)
[Image: see text] Studying the atomic structure of intrinsic defects in two-dimensional transition-metal dichalcogenides is difficult since they damage quickly under the intense electron irradiation in transmission electron microscopy (TEM). However, this can also lead to insights into the creation of defects and their atom-scale dynamics. We first show that MoTe(2) monolayers without protection indeed quickly degrade during scanning TEM (STEM) imaging, and discuss the observed atomic-level dynamics, including a transformation from the 1H phase into 1T′, 3-fold rotationally symmetric defects, and the migration of line defects between two 1H grains with a 60° misorientation. We then analyze the atomic structure of MoTe(2) encapsulated between two graphene sheets to mitigate damage, finding the as-prepared material to contain an unexpectedly large concentration of defects. These include similar point defects (or quantum dots, QDs) as those created in the nonencapsulated material and two different types of line defects (or quantum wires, QWs) that can be transformed from one to the other under electron irradiation. Our density functional theory simulations indicate that the QDs and QWs embedded in MoTe(2) introduce new midgap states into the semiconducting material and may thus be used to control its electronic and optical properties. Finally, the edge of the encapsulated material appears amorphous, possibly due to the pressure caused by the encapsulation.